(untitled) (MAUSAM, 1982)
Time variations of currents, temperatures and salinities at specified depths from surface to 1000 m have been studied using the hydrographic and current data collected by the USSR research ships at northern and southern locations of the central Arabian Sea polygon of Monsoon- 77 experiment. The results are discussed in relation to the onset and progress of the summer monsoon. The influence of a severe cyclonic storm on the variation of thermal structure in the surface layers is also discussed.